13, each term is the sum of two preceding ones.
Answer:
C. -7x^2 - 28
Step-by-step explanation:
Firstly simplify the bracket before doing anything;
4x(3x - 7) = 12x^2 - 28x
then go back to the question and substitute the expression(12x^2 - 28x) on the bracket and then work out the question;
12x^2 - 28x -19x^2...then group the values with the same exponent of x,
(12x^2 - 19x^2) - 28x
; -7x^2 - 28x
Which number is the under lined digit?
Step-by-step explanation:
Since y is directly proportional to x,
we have y = kx, where k is a real constant.
When x = 15, y = 12.
=> (12) = k(15), k = 0.8.
Therefore we have y = 0.8x.
When x = 2, y = 0.8(2) = 1.6.
The answer is y = 1.6 when x = 2.